Assessment Study of Factors Associated With Successful ‎Trial of Labor After The First Cesarean Section - العامودي بشرى; لؤي حسن; ثورة نعيسة (Latakia University Journal -Medical Sciences Series, 2022)
Objective: Determine the effectiveness of experience of labor after the first caesarean and factors associated with its success and reduce the rate of caesarean sections in patients with single caesarean section and accompanying complications. Methods and Materials: A case-control prospective study was conducted on pregnant women with one previous Caesarean section and multi-birth pregnant women had single caesarean section were admitted to Tishreen University Hospital and will be subjected to labor for one year from (1-1-2021) until (31-12-2021). Results: The study sample amounted to 196 pregnant women, which were divided into cases group “who experienced successful labor”: (133) women (67.96%), and control group “who had a repeat caesarean section”: (63) women (32.04%). The mean age was similar in the two groups. Our study showed that pregnant women with a previous single birth had a significantly lower rate of vaginal delivery. Whereas, patients with gestational age greater than 40 weeks had higher rate of repeat caesarean section. It was found that the value of the Bishop Score (less than 4) was associated with significantly lower rate of vaginal delivery success. we found that success of the labor trial was significantly higher in group of pregnant women whose newborn weight was between (3000-3499 grams). Defective presentations were the primary reason for the first caesarean section in both groups. The interval of less than two years between previous cesarean section and current pregnancy was associated with insignificantly lower rate of successful vaginal delivery. Conclusion: The chance of successful labor experience increases in women with a single previous caesarean whose ages between (20-40) years, and in women with fetal weight (3000-3499 g), who had Bishops Score equals (4) or more, and women with history of (2-4) vaginal births, and who have had interval of more than 2 years.